2016
DOI: 10.1039/c5cp05890b
|View full text |Cite
|
Sign up to set email alerts
|

Luminescence turn-on/off sensing of biological iron by carbon dots in transferrin

Abstract: Iron is a key nutrient as well as a potential toxin for almost all living organisms. In mammalian cells, serum transferrin (Tf) is responsible for iron transport and its iron overload/deficiency causes various diseases. Therefore, closely regulated iron homeostasis is extremely essential for cellular metabolism. In the present article we report the pH-dependent luminescence turn-on/off sensing of bound Fe(3+) ions of serum Tf by carbon dots (CDs) with the help of photoluminescence (PL) spectroscopy, FTIR spect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 78 publications
0
22
0
Order By: Relevance
“…However, the slope for holo-Tf is −0.048 RFU/µM, revealing a direct proportionality between the extent of fluorescence quenching of the CDs signal and the concentration of holo-Tf. In work by Bhattacharya and colleagues [39] a similar effect was characterized as static quenching via their steady-state and time-resolved photoluminescence measurements at pH 7.4. Based on estimated thermodynamic parameters of the CD-Tf association determined from quenching measurements performed at various temperatures, they concluded that the observed quenching was a result of the electrostatic interaction between CDs and the Fe 3+ ions associated with holo-Tf, not the amino acid residues.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the slope for holo-Tf is −0.048 RFU/µM, revealing a direct proportionality between the extent of fluorescence quenching of the CDs signal and the concentration of holo-Tf. In work by Bhattacharya and colleagues [39] a similar effect was characterized as static quenching via their steady-state and time-resolved photoluminescence measurements at pH 7.4. Based on estimated thermodynamic parameters of the CD-Tf association determined from quenching measurements performed at various temperatures, they concluded that the observed quenching was a result of the electrostatic interaction between CDs and the Fe 3+ ions associated with holo-Tf, not the amino acid residues.…”
Section: Resultsmentioning
confidence: 99%
“…There are four possible conformations of Tf, depending on the number and position of bound Fe 3+ ions: (i) holo-Tf (fully metallated), (ii) single Fe 3+ bound only to the C-lobe or (iii) only to the N-lobe (partially metallated), and (iv) apo-Tf (demetallated). The Tf receptor is overexpressed on proliferating cancer cells, but not normal cells; therefore, Tf is a promising carrier protein for targeted drug delivery and therapy for cancerous cells [31,32,33,34,35,36,37,38,39]. The ability to separate the different conformations of Tf (fully metallated, partially metallated, and demetallated), is important because potential drug molecules may have different affinities for the different conformations of Tf.…”
Section: Introductionmentioning
confidence: 99%
“…Hydrophilicity, easy preparation and environmental friendliness are some of their additional notable features . Optical imaging and sensing are potential areas of their application . These properties and applications make them distinct from and superior to commonly used organic fluorophores and quantum dots.…”
Section: Introductionmentioning
confidence: 99%
“…[12] Optical imaging and sensing are potential areas of their application. [13][14][15][16][17][18][19] These properties and applications make them distinct from and superior to commonly used organic fluorophores and quantum dots.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7][8] In addition, they are extremely detrimental to living organisms for example algae, bacteria, fungi and viruses. In recent years, carbon dots, a new class of carbonaceous and fluorescent nanomaterials with spherical shape and size below 10 nm, 27 have attracted much attention for their unique characteristics, like much more sources of raw materials, easily synthetic method, high quantum yield, excellent optical and chemical stabilities, easy surface-functionalization, low toxicity, good water-solubility and biocompatibility, 28,29 and have been applied to determine many substances, for instance, DNA, nitrite, hypochlorite, ascorbic acid, 6-mercaptopurine, superoxide anion, pH, H 2 S, metal ions, etc. The traditional measurement methods of Cu 2+ include colorimetric method, capillary electrophoresis, atomic absorption spectroscopy (AAS), inductively coupled plasma mass spectrometry (ICP-MS), surface-enhanced Raman scattering, polarography, chemiluminescent method, electrochemical method and so on, 10-20 but these methods require time-consuming pretreatments, tedious procedures, organic reagents, complex and expensive instrumentations, etc.…”
Section: Introductionmentioning
confidence: 99%